PENERAPAN TA’ZIR DALAM MEMBENTUK KARAKTER DISIPLIN SANTRI PUTRA DI PONDOK PESANTREN TANWIRUL QULUB DESA SUNGELEBAK, KECAMATAN KARANGGENENG, KABUPATEN LAMONGAN - Ainul Yaqin, Ahmad; Sun'iyah, Siti Lathifatus (Fakultas Agama Islam, 2026)
Islamic boarding schools are Islamic educational institutions where students study the Al-Qur'an, Hadith, fiqh, morals and other Islamic knowledge, both formally and non-formally. Apart from functioning as a place for religious education, Islamic boarding schools also shape the character and personality of students. However, one of the problems that often arises is the low level of discipline among students, which results in non-compliance with rules, weak motivation to learn, and lack of responsibility. Discipline is an important value that reflects obedience, order, and a sense of responsibility. To instill these values, Islamic boarding schools implement a ta'zir system. The aims of this research are: (1) to describe the application of ta'zir at the Tanwirul Qulub Islamic Boarding School, Sungelebak Village, Karanggeneng District, Lamongan Regency. (2) To describe the application of ta'zir in shaping the disciplined character of male students at the Tanwirul Qulub Islamic Boarding School, Sungelebak Village, Karanggeneng District, Lamongan Regency, The method used in this research is a qualitative approach with a case study type. Data collection techniques include; observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. The research results show that the implementation of ta'zir at the Tanwirul Qulub Islamic Boarding School is educational and proportional, through verbal warnings, additional assignments, spiritual formation, and social sanctions. Ta'zir is carried out educationally, taking into account the condition and psychology of the students, so that they realize their mistakes and do not repeat them. Ta'zir has been proven to be effective in forming discipline, responsibility, obedience and self-control. Students who are subjected to ta'zir show positive changes in behavior and worship. In the long term, ta'zir fosters moral awareness, self-control and discipline as part of character, as well as providing a preventive effect on other students.